Structural adequacy for residential complex in Barquisimeto city. Venezuela (Gaceta Técnica, 2016)
The structural analysis and reinforcement project is presented for a city complex consisting of 31 houses with obvious signs of failure, built in the city of Barquisimeto in 2008 on unconstrained land. The results of the analysis showed insufficient responsiveness to service stresses, high seismic vulnerability, and deficiencies in the amount and distribution of reinforcing steel. The reinforcement of the superstructure was proposed by means of the construction of panel walls, and micro piles and / or reinforced solid slab for the infrastructure, using values of resistance of the concrete obtained in the destructive tests, soil parameters from the geotechnical study and the settlements Differentials derived from topographic leveling.
Keywords: structural vulnerability; earthquake